Phosphine ligands in heck coupling reaction / Wan Aziyani Yazmin Wan Yeit - Wan Yeit, Wan Aziyani Yazmin (2007)
Phosphine ligands have been used as ligands in Heck reaction to produce stilbene. Nevertheless different ligands used in a reaction may produce different yields and effect of desired compound. Therefore, the aim of the research was to study the effect of different phosphine ligands in Heck coupling reaction. Heck reactions were done by using 4 different ligands, tri-o-tolylphosphine, tetraphenylphosphonium chloride, methyl triphenylphoshponium iodide and tetrakis (tripheynlphosphonium) palladium with para iodophenol and para-chlorostyrene as the starting materials. The yields of the desired compound are 33.85%, 70.29%, 6.51 % and 11.43% respectively. The products in each reaction were analyzed using TLC and extracted using ethyl acetate and hexane. Purification of the reaction products was done by using column chromatography. The desired compound was sent for NMR analysis for structure characterization. The spectra were recorded using 1H-NMR spectrometer in order to elucidate the structure of the compound. IR absorption was also used to analyze the structure characterization.